Pemanfaatan Aplikasi Kecerdasan Artifisial Untuk Kegiatan Pembelajaran Di Pesantren Ma’rifa Cigalontang Kabupaten Tasikmalaya - Evi Dewi Sri Mulyani; Ariel Ivan Al-Hakim; Fauzan M. Iqbal; Teguh Ikhlas Ramadhan; Agus Supriatman; Dede Syahrul Anwar; Rudi Hartono; Missi Hikmatyar; Cepi Rahmat Hidayat; Aso Sudiarjo; Ruuhwan; Shinta Siti Sundari; Teuku Mufizar; Widia Nurindriyanti (JPPkM: Jurnal Pengabdian dan Pemberdayaan kepada Masyarakat, 2026)
The rapid advancement of Large Language Model (LLM)-based Artificial Intelligence (AI) has created new opportunities to improve the quality and efficiency of teaching and learning processes. However, the adoption of this technology remains constrained by limited AI literacy and prompt engineering skills among educators, particularly in Islamic boarding schools (pesantren). This community service program aimed to enhance teachers' knowledge and skills in utilizing LLM applications through training on prompt engineering techniques based on the C.R.E.A.T.E. and S.T.A.R. frameworks. The program was conducted at Ma'rifa Islamic Boarding School in Cigalontang, Tasikmalaya Regency, involving 32 participants. The implementation methods included lectures, AI application demonstrations, hands-on prompt development practice, and evaluations through pre-tests, post-tests, practical assessments, and participant satisfaction questionnaires. The evaluation results showed that the participants' average score increased from 58.4 in the pre-test to 85.7 in the post-test, representing an improvement of 46.7%. In the practical assessment, 82% of participants successfully developed prompts using the C.R.E.A.T.E. and S.T.A.R. techniques with good to excellent performance. Furthermore, the participant satisfaction survey yielded an average score of 4.58 out of 5, indicating that the training materials were considered relevant, easy to understand, and beneficial for supporting teaching and learning activities. Overall, the program successfully improved participants' AI literacy, understanding of LLM technology, and prompt engineering competencies. Therefore, similar training programs should be implemented continuously to support digital transformation and foster innovation in teaching and learning within Islamic boarding school environments.